Research on the Regional Environmental Protection and Imbalance of Economic Development in Qinghai Province. Issue 1 (February 2021) - Qing, Xin; Li, Juanyi; Zhao, Falan
Abstract: Due to differences in economic foundation, natural and geographical environment, and other factors, the regional economic development of Qinghai Province is unbalanced, and regional environmental protection is problematic. This paper uses the location entropy method and the coupling coordination model to evaluate the economic development and environmental protection of eight regions in Qinghai Province. Finally, combining the characteristics of economic development and natural environment in the main areas of Qinghai Province, corresponding countermeasures and suggestions are put forward.